2013
DOI: 10.1186/1472-6882-13-93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba on chemically-induced mammary tumors in rats receiving tamoxifen

Abstract: BackgroundGinkgo biloba extract (GbE) is used extensively by breast cancer patients undergoing treatment with Tamoxifen (TAM). Thus, the present study investigated the effects of GbE in female Sprague–Dawley (SD) rats bearing chemically-induced mammary tumors and receiving TAM.MethodsAnimals bearing mammary tumors (≥1 cm in diameter) were divided into four groups: TAM [10 mg/kg, intragastrically (i.g.)], TAM plus GbE [50 and 100 mg/kg, intraperitoneally (i.p.)] or an untreated control group. After 4 weeks, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…The cytochemical carcinogen, DMBA is a widely used agent for inducing breast carcinoma in experimental models and it effects either by initiating or promoting mutations in carcinogenesis responsible genes . In a study conducted by Kabel et al, it was used 80 mg/kg DMBA to induce breast cancer and was observed the levels of selected antioxidant in DMBA group were lower compared with therapeutic groups …”
Section: Discussionmentioning
confidence: 99%
“…The cytochemical carcinogen, DMBA is a widely used agent for inducing breast carcinoma in experimental models and it effects either by initiating or promoting mutations in carcinogenesis responsible genes . In a study conducted by Kabel et al, it was used 80 mg/kg DMBA to induce breast cancer and was observed the levels of selected antioxidant in DMBA group were lower compared with therapeutic groups …”
Section: Discussionmentioning
confidence: 99%
“…The side influence of tamoxifen has been perceived via recent studies. Numerous clinical studies have focused on discovering complementary substances that can synergize and diminish the side influences of tamoxifen (Yaacob et al 2014;Dias et al 2013). The beneficial relationship among tamoxifen and certain nutrients have been determined to reduce the medicinal side influences of tamoxifen amelioration or prevention (Tham et al 1998).…”
Section: Groupmentioning
confidence: 99%
“…Recent studies have shown that GBE restrains estrogen-sensitive breast cancer by inhibiting aromatase and estrogen production (Park et al, 2015 , 2016 ), restrains the proliferation of ER-negative breast cancer cells independently of the ERs (Park et al, 2013 ; Zhao et al, 2013 ). Additionally, GBE has a synergistic effect with tamoxifen (Dias et al, 2013 ).…”
Section: Chinese Herbal Extractsmentioning
confidence: 99%